Optimalisasi Kinerja Aparat Desa di Desa Mekong Melalui Pelatihan Teknologi Informasi - Gemawati, Sri; Marjulisa, M Rike; Putri, Ayunda; Ali, Irsan Taufik; Rasdana, Oki (Unri Conference Series: Community Engagement, 2024)
In the digital era, skills in using Microsoft Office are very important for village officials. This is the background of the Microsoft Office training for village officials in Desa Mekong, Kecamatan Tebing Tinggi Barat, Kepualauan Meranti. The training materials include Microsoft Word, Excel, and Power Point. This training uses the “Learning by Doing” method which allows participants to immediately engage in practice after the presentation of the material. Participating village officials showed significant improvement in knowledge and skills using Microsoft Office. The enthusiasm of the participants and the assistance by the students also enriched the learning process, making it more interactive and in-depth. This training has positive implications for improving the competence of village officials and the quality of public services in Desa Mekong.